2014
DOI: 10.12968/jowc.2014.23.11.552
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling increasing wound care demands with available resources

Abstract: Demographic and epidemiological data suggest that health-care demand will increase considerably in the future as a result of an ageing population and a rise in the prevalence of chronic diseases such as diabetes. This phenomenon has come to be referred to as the 'health care time bomb' in the popular press and political discourse. The authors seek to look beyond the headlines and political rhetoric to clarify the extent to which they reflect the likely future reality with a specific focus on wound management. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 4 publications
0
24
0
Order By: Relevance
“…This trend is clearly unsustainable, and as a result, it is vital that health care providers seek more efficient ways of managing a resource‐intensive casemix with increasingly complex needs, such as patients with a wound.
Wound management is estimated to account for over 50% of community nurse time in European studies, with patients often having three or more home health visits per week .The demands on nurse time are expected to increase further because of earlier hospital discharge, ageing populations and increasing rates of morbidities associated with wounds .For example, the International Diabetes Foundation estimates that worldwide diabetes prevalence will continue to increase to 9·9% by 2030 .Diabetic patients have up to a 25% lifetime risk of developing a foot ulcer .The increasing demands on nurse time will become unsustainable if the present trend continues, and health systems need to identify more efficient ways of managing the increased workload.
Question: Are there any estimates of how much demand for wound management services will increase?Answer: Yes, in some countries. For example, in 2010, it was estimated that the cost of wound management in municipalities in Denmark was DKK 735 m (18 000 wounds per year requiring over 3 m dressing changes).
…”
Section: The Impact Of Wounds On the Health System – A Growing Challengementioning
confidence: 99%
See 2 more Smart Citations
“…This trend is clearly unsustainable, and as a result, it is vital that health care providers seek more efficient ways of managing a resource‐intensive casemix with increasingly complex needs, such as patients with a wound.
Wound management is estimated to account for over 50% of community nurse time in European studies, with patients often having three or more home health visits per week .The demands on nurse time are expected to increase further because of earlier hospital discharge, ageing populations and increasing rates of morbidities associated with wounds .For example, the International Diabetes Foundation estimates that worldwide diabetes prevalence will continue to increase to 9·9% by 2030 .Diabetic patients have up to a 25% lifetime risk of developing a foot ulcer .The increasing demands on nurse time will become unsustainable if the present trend continues, and health systems need to identify more efficient ways of managing the increased workload.
Question: Are there any estimates of how much demand for wound management services will increase?Answer: Yes, in some countries. For example, in 2010, it was estimated that the cost of wound management in municipalities in Denmark was DKK 735 m (18 000 wounds per year requiring over 3 m dressing changes).
…”
Section: The Impact Of Wounds On the Health System – A Growing Challengementioning
confidence: 99%
“…The demands on nurse time are expected to increase further because of earlier hospital discharge, ageing populations and increasing rates of morbidities associated with wounds .…”
Section: The Impact Of Wounds On the Health System – A Growing Challengementioning
confidence: 99%
See 1 more Smart Citation
“…This may not have been an issue before, but now the exponential increase in acute, chronic and post-surgical wound care costs predicted in most of the health care systems of countries, including the United Kingdom and United States have risen extensively. [1,11,15,20,21] Suitable care and management of wounds can prevent the progression into chronic wounds. [15] It has been observed that it is not always the most expensive wound care products that advance wound healing, but rather emphasis is placed on moist topical wound care (alginates, antimicrobials, etc).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic wounds, which include diabetic, venous, and pressure ulcers, are a significant global problem, causing patient morbidity and a substantial financial burden on health services worldwide. The incidence of chronic wounds is currently rising because those populations most susceptible, the elderly and diabetic, are rapidly expanding . This in turn puts increasing financial strain on health services.…”
mentioning
confidence: 99%